CPCP: Colorado Plateau Coring Project – 100 Million Years of Early Mesozoic Climatic, Tectonic, and Biotic Evolution of an Epicontinental Basin Complex - John W. Geissman; Dennis V. Kent; Paul E. Olsen (Scientific Drilling, 2008)
Early Mesozoic epicontinental basins of western North America contain a spectacular record of the climatic and tectonic development of northwestern Pangea as well as what is arguably the world’s richest and most-studied Triassic-Jurassic continental biota. The Colorado Plateau and its environs (Fig. 1) expose the textbook example of these layered sedimentary records (Fig. 2). Intensely studied since the mid-nineteenth century, the basins, their strata, and their fossils have stimulated hypotheses on the development of the Early Mesozoic world as reflected in the international literature. Despite this long history of research, the lack of numerical time calibration, the presence of major uncertainties in global correlations, and an absence of entire suites of environmental proxies still loom large and prevent integration of this immense environmental repository into a useful global picture. Practically insurmountable obstacles to outcrop sampling require a scientific drilling experiment to recover key sedimentary sections that will transform our understanding of the Early Mesozoic world.